2019
DOI: 10.1039/c8en01167b
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic framework-based nanomaterials for adsorption and photocatalytic degradation of gaseous pollutants: recent progress and challenges

Abstract: Design and engineering of metal–organic frameworks for the adsorption/degradation of inorganic toxic gases, organic vapors and particulate matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
115
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(115 citation statements)
references
References 155 publications
0
115
0
Order By: Relevance
“…Recent years have seen an enormous amount of research highlighting oxygenated volatile organic compounds (OVOCs) owing to their threats to human health and the environment. [1][2][3][4] Among various OVOCs, acetone is one of the most promising research candidates for various industrial and medical applications, not least towards diabetes diagnosis [5][6][7] in human exhaled breath. Clinical analysis has shown that the acetone concentration in the exhaled breath of healthy people is 300-900 ppb, while it will increases to more than 1.8 ppm for diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have seen an enormous amount of research highlighting oxygenated volatile organic compounds (OVOCs) owing to their threats to human health and the environment. [1][2][3][4] Among various OVOCs, acetone is one of the most promising research candidates for various industrial and medical applications, not least towards diabetes diagnosis [5][6][7] in human exhaled breath. Clinical analysis has shown that the acetone concentration in the exhaled breath of healthy people is 300-900 ppb, while it will increases to more than 1.8 ppm for diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the adsorption technique is not very effective as it causes secondary pollution during the recycling of adsorbents. 3,4 On the contrary, the use of heterogeneous photocatalysis for the degradation of organic pollutants in the presence of light irradiation has emerged as an alternative environmentally benign solution for this problem. The use of sunlight as a source for this process, good degradation of pollutants and excellent recyclability of photocatalysts are the key advantages of this process, which makes it a sustainable approach.…”
Section: Introductionmentioning
confidence: 99%
“…[ 63–65 ] Therefore, efficient utilization of solar light by MOFs can be facilely realized by modifications on either the metal ions or the organic linkers, especially considering the availability of the large variety of organic ligands and the rich coordination chemistry of the metal cations, which results in almost unlimited MOF structures. [ 66,67 ] With all these advantages, MOFs have been successfully applied in a variety of photocatalytic reactions, including CO 2 reduction, [ 68–71 ] hydrogen evolution, [ 72–76 ] pollutant degradations, [ 77–81 ] as well as organic transformation. [ 36,82–84 ]…”
Section: Introductionmentioning
confidence: 99%